2014
DOI: 10.1039/c4cy00719k
|View full text |Cite
|
Sign up to set email alerts
|

An improved catalytic system for the reduction of levulinic acid to γ-valerolactone

Abstract: An improved bidentate phosphine-modified Ru catalytic system was developed for the selective reduction of levulinic acid to γ-valerolactone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 28 publications
2
41
2
1
Order By: Relevance
“…Among the platform molecules levulinic acid could play a key role in the chain [43], since it is the raw material of a proposed platform chemical (gamma-valerolactone) that can be obtained by its selective hydrogenation [44][45][46][47][48]. Extending the queue a new product, biopolymer generation was established by Tanamool [49] at laboratory scale.…”
Section: Introductionmentioning
confidence: 99%
“…Among the platform molecules levulinic acid could play a key role in the chain [43], since it is the raw material of a proposed platform chemical (gamma-valerolactone) that can be obtained by its selective hydrogenation [44][45][46][47][48]. Extending the queue a new product, biopolymer generation was established by Tanamool [49] at laboratory scale.…”
Section: Introductionmentioning
confidence: 99%
“…GVL can also be produced directly from C 6 sugars using an acid catalyst (trifluoroacetic acid) in combination with a heterogeneous hydrogenation catalyst (Ru/C) without isolation of LA . The utilization of recyclable Ru‐based catalysts for solvent‐free homogeneous catalytic hydrogenation of LA to GVL, and the energy efficient continuous production of GVL from LA using a heterogeneous continuous‐flow reactor equipped with 5 % Ru/C is reported . Furthermore, the aqueous phase catalytic hydrogenation of LA to produce GVL by homogeneous Ru complexes is also reported in the literature .…”
Section: Methodsmentioning
confidence: 99%
“…[28][29][30][31] In early pioneering studies Osakada et al, [32] showed the activation of C-O bonds of five membered cyclic anhydride, aldehydic and keto acids using two different ruthenium ( [10] demonstrated the use of an in situ generated Ru catalyst using a combination of Ru(acac) 3 and the strongly electron donating phosphine P n Bu 3 in the presence of NH 4 PF 6 for LA hydrogenation to GVL ( [33] reported the effect of the mondentate and chelating phosphines: trioctylphosphine (P n Oct 3 ), 1,4-diphenylphosphinobutane (DPPB) and triphos ( fig. 2) and various acidic additives for the transformation of LA.…”
Section: Hydrogenation Of Levulinic Acid (La) To γ-Valerolactone (Gvl)mentioning
confidence: 99%
“…The activity of a range of bidentate diphosphine-Ru based catalysts, generated in situ form Ru(acac) 3 , for LA to GVL conversion has been investigated by the same group [30] (fig. 5) and compared to the sulfonated monodenate phosphine ligand Ru(acac) 3 / n Bu-DPPDS system.…”
Section: Hydrogenation Of Levulinic Acid (La) To γ-Valerolactone (Gvl)mentioning
confidence: 99%